2020
DOI: 10.3389/fmicb.2020.541972
|View full text |Cite
|
Sign up to set email alerts
|

Metagenomic Characterization of the Microbiome and Resistome of Retail Ground Beef Products

Abstract: Ground beef can be a reservoir for a variety of bacteria, including spoilage organisms, and pathogenic foodborne bacteria. These bacteria can exhibit antimicrobial resistance (AMR) which is a public health concern if resistance in pathogens leads to treatment failure in humans. Culture-dependent techniques are commonly used to study individual bacterial species, but these techniques are unable to describe the whole community of microbial species (microbiome) and the profile of AMR genes they carry (resistome),… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(8 citation statements)
references
References 42 publications
(55 reference statements)
1
7
0
Order By: Relevance
“…Production system differences in carcass meat trimmings were not apparent in predominant classes of AMR. This finding was similar to another targeted shotgun metagenomic study [45] that compared conventional to raised-without-antibiotics ground beef that also found no differences in the predominant classes of resistance between the two groups (in this case 91% of the resistance gene were associated with tetracycline resistance). In a culture-based study, when conventional versus organic beef has been evaluated in terms of AMR, Escherichia coli and Staphylococcus aureus were found to harbor lower rates of AMR in organic versus conventional beef samples; although, no production differences were found in Listeria monocytogenes isolates [46].…”
Section: Discussionsupporting
confidence: 87%
“…Production system differences in carcass meat trimmings were not apparent in predominant classes of AMR. This finding was similar to another targeted shotgun metagenomic study [45] that compared conventional to raised-without-antibiotics ground beef that also found no differences in the predominant classes of resistance between the two groups (in this case 91% of the resistance gene were associated with tetracycline resistance). In a culture-based study, when conventional versus organic beef has been evaluated in terms of AMR, Escherichia coli and Staphylococcus aureus were found to harbor lower rates of AMR in organic versus conventional beef samples; although, no production differences were found in Listeria monocytogenes isolates [46].…”
Section: Discussionsupporting
confidence: 87%
“…Similar to the above, this study found that product management had a greater influence on the ground beef microbiome than the resistome. Furthermore, the novel target-enriched shotgun sequencing implemented in this study allowed for the analysis of samples with low microbial abundance [40].…”
Section: Next-generationation Sequencing Methodsmentioning
confidence: 99%
“…Current research on foodborne bacteria primarily focuses on individual pathogens and identifier microbes [24]. ARGs allow bacteria to survive throughout the face of antibiotics, and the resistance to antibiotics is reliably evaluated by phenotypic testing of isolates to a variety of antibiotics in food microbiology labs [25].…”
Section: Introductionmentioning
confidence: 99%